Treatment outcomes of drug-resistant tuberculosis in people living with HIV in Odesa province, Ukraine, 2014-2016 - Svitlana Yesypenko; Ruzanna Grigoryan; Yulia Sereda; Olga Denisuk; Liana Kovtunovich; Tatyana Rybak; Oleksandr Postnov; Oleksandr Neduzhko; Sergiy Antonyak; Valentina Bespoyasnaya (Journal of Infection in Developing Countries)
Introduction: Odesa province has the highest TB/HIV prevalence in Ukraine, exceeding the total prevalence in the country by 3 times. The objective of this study was to investigate the unfavorable treatment outcomes and associated factors in patient with drug-resistant (DR) TB in people living with HIV (PLH) in Odesa.